Aconitine-containing agent enhances antitumor activity of dichloroacetate against Ehrlich carcinoma - Pyaskovskaya, O.N.; Boychuk, I.V.; Fedorchuk, A.G.; Kolesnik, D.L.; Dasyukevich, O.I.; Solyanik, G.I. (Experimental Oncology, 2015)
Significant variability of anticancer efficacy of dichloroacetate (DCA) stimulated an active search for the agents capable to enhance it antitumor action. Therefore, the aim of this work is the study of capability of aconitine-containing antiangiogenic agent BC1 to enhance anticancer activity of DCA against Ehrlich carcinoma. Materials and Methods: DCA (total dose was 1.3 g/kg of b.w.) and BC1 (total dose was 0.9 mg/kg of b.w.) were administered per os starting from the 2nd and 3rd days, respectively (8 administrations for each agent). Antitumor efficacy of agents was estimated. Lactate level, LDH activity and the state of mitochondrial electron transport chain in tumor cells as well as phagocytic activity and reactive oxygen species (ROS) production of tumor-associated macrophages (TAM) were studied. Results: Combined administration of DCA and ВС1 resulted in 89.8% tumor growth inhibition (p < 0.001), what is by 22.5% (p < 0.05) higher that that of DCA alone. This combined treatment was accompanied with a decrease of lactate level in tumor tissue by 30% (p < 0.05) and significant elevation of LDH activity by 70% (p < 0.01). Increased level of NO-Fe-S clusters and 2-fold reduction of Fe-S cluster content were revealed in tumor tissue of mice after DCA and BC1 administration. It was shown that combined therapy did not effect TAM quantity and their phagocytic activity but stimulated ROS production by TAMs by 78% (p < 0.05) compared to this index in control animals. Conclusion: Antiangiogenic agent ВС1 in combination with DCA considerably enhances antitumor activity of DCA via significant decrease of Fe-S-containing protein level resulted from substantial elevation of nitrosylation of these proteins. Key Words: Ehrlich carcinoma, dichloroacetate, aconitine-containing agent, tumor-associated macrophages, mitochondrial electron transport chain.